Improving the Science Program. - Blough, Glenn O. (Educational Leadership, 1962)
The article presents information on the need to improve science teaching methods in the United States. Several school systems are assessing their science offerings, methods of instruction, and materials available. Courses of study or curriculum guides are appearing. Summer and yearlong institutes for the training of in-service teachers are being sponsored by various interested groups and these are definitely raising the standards of instruction for those who participate. Through the National Defense Education Act, large amounts of apparatus have become available for schools. Yet progress comes through an analysis of needs and devising a program for meeting them, and not through dwelling on the faults. It seems appropriate, then, to take inventory to discover the needs and concentrate on plans to meet them. Science is a method of discovery--it is a creative intellectual activity--it is learning how to find the answers--it is an attitude-and it is the body of organized subject matter that is the result of this intellectual activity. Understanding this is the first step toward achieving a real science program.